Peningkatan Efisiensi Penggunaan Bahan Bakar Kendaraan Bermotor Dengan Melakukan Pencarian Jarak Terdekat Menggunakan Jaringan Syaraf Tiruan Hopfield Di Wilayah Purwokerto - Agung Mubyarto; Hesti Susilawati (Jenderal Soedirman University, 2010)
This proposed research concern with application of continuous Hopfield neural networks for shortest path routing in a given map, in this case Purwokerto city’s map had choosen as an example. The method that was used in this research based on the ability of continuous Hopfield neural networks for representing their neuron as choosen vertices in the given map. The result shows that the networks can produce optimal route for such source and destination node pairs. As the product of this research, we have knowledge about the shortest way from one to another location at Purwokerto, so we can increase the efficiency on fuel use by using this route